Effect Of Confronting Brand And Experience Of Brand On Remembering Brand (Case Study: Consumers Of Shampo In Rasht) - Abkenarei, Mahsa Ghaffari; Asil, Seyyed Mohammad Noe Pasand (The Turkish Online Journal of Design Art and Communication, 2016)
Present research aims to investigate The Effect of Brand Exposure and Brand Exprience on Brand Recall through perceived brand image, self-image congruence and trust. This study is descriptive and in aim is functional and in terms data collection is field. Data collecting tool is questionnaire which contains 21 questions to measure the research variables. To measuring the variables from the whole 5-point Likert was used. Reliability using Cronbach's alpha was reviewed and approved. The population of the study is all Shampoo Consumers in Rasht. Using a Cochran formula 390 subjects were evaluated for the study. To test the hypothesis, methods of structural equation modeling was used. The results showed that Brand Exposure has a Psitive and significant effect on perceived brand image and self-image congruence. While has not significant effect on trust. On the other hand, Brand Exprience has a positive and significant effect on all three variables such perceived brand image, self-image congruence and trust. Also all three mediating variables has a significant effect on brand recall.
Keywords: Brand Exposure; Brand Exprience; Brand Image; Self-image Congruence; Trust; Brand recall